2010
DOI: 10.1007/s10590-010-9070-9
|View full text |Cite
|
Sign up to set email alerts
|

Eye tracking as an MT evaluation technique

Abstract: Eye tracking has been used successfully as a technique for measuring cognitive load in reading, psycholinguistics, writing, language acquisition etc for some time now. Its application as a technique for automatically measuring the reading ease of MT output has not yet, to our knowledge, been tested. We report here on a preliminary study testing the use and validity of an eye tracking methodology as a means of semiand/or automatically evaluating machine translation output. 50 French machine translated sentences… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 84 publications
(35 citation statements)
references
References 9 publications
0
35
0
Order By: Relevance
“…382). Therefore, longer mean fixation durations within the same activity could reflect increased cognitive processing and cognitive load (Kruger et al, 2015), a finding consistently reported in other studies (e.g., Doherty & O'Brien, 2014;Doherty, O'Brien, & Carl, 2010). In this regard, however, it is important to consider that activities like reading tend to elicit more, shorter fixations than scene perception, which elicits fewer, longer fixations (cf.…”
Section: Eye Movementsmentioning
confidence: 70%
“…382). Therefore, longer mean fixation durations within the same activity could reflect increased cognitive processing and cognitive load (Kruger et al, 2015), a finding consistently reported in other studies (e.g., Doherty & O'Brien, 2014;Doherty, O'Brien, & Carl, 2010). In this regard, however, it is important to consider that activities like reading tend to elicit more, shorter fixations than scene perception, which elicits fewer, longer fixations (cf.…”
Section: Eye Movementsmentioning
confidence: 70%
“…Cognitive processing and effort can be studied via gaze data, building on the eye-mind hypothesis by Just and Carpenter (1980). An increased number of fixations (Doherty, O'Brien, et al 2010) or higher average fixation durations (Carl, Dragsted, Elming, et al 2011) have been used as indicators of increased cognitive processing. O'Brien (2007) compared human translation with post-editing and translation memory (TM) matches and found postediting to be less cognitively demanding than human translation.…”
Section: Post-editing Vs Human Translationmentioning
confidence: 99%
“…O'Brien (2007) compared human translation with post-editing and translation memory (TM) matches and found postediting to be less cognitively demanding than human translation. Doherty, O'Brien, et al (2010) used eye-tracking to identify MT comprehensibility and discovered that the total gaze time and number of fixations correlate well with MT quality. When considering the difference between source text processing and target text processing, findings become more complicated.…”
Section: Post-editing Vs Human Translationmentioning
confidence: 99%
“…The current study builds upon previous work conducted by the researchers in which the usefulness of eye tracking as a semi-automatic method for the evaluation of MT output was investigated (Doherty and O'Brien, 2009;Doherty et al, 2010, Doherty andO'Brien, 2012), in addition to the effects of controlled authoring 1 on the readability and comprehension of MT output (O'Brien, 2010;Doherty, 2012). Related work includes that of Tomita (1992) and Tomita et al (1993), who examined the comprehension of MT output, and of Fuji (1999), who, in addition to this measure, included informativeness and fluency.…”
Section: Introductionmentioning
confidence: 97%